Serum Lipid-Lowering in Rats Fed with High Dietary Fiber from Cereal and Nata De Coco - Wanpen Mesomya; Yaovadee Cuptapun; Duangchan Hengsawadi; Plernchai Tangkanakul; Pongsri Jittanoonta; Ratana Pakpeankitvatana (Agriculture and Natural Resources, 2002)
This study was conducted to evaluate the different serum triglyceride and cholesterol-lowering effects of five kinds of dietary fiber diet in xperimental rats. Source and percentage of dietary fiber in five experimental diets were 2.86 from unpolished rice, mung bean, sweet corn and nata de coco in diet 1 and 2, 7.76 from apple pectin in diet 3, 10.39 from cellulose in diet 4, 0.58 in diet 5. Each diet was composed of soy oil, salt mixture, vitamin mixture, corn starch and sucrose. Cholesterol contents were 13.00, 11.40, 14.20, 14.10 and 13.50 mg/100 g in diet 1, 2, 3, 4 and 5, respectively. Those five experimental diets were fed to 3-wk-old weanling male Sprague-Dawley rats for 4 weeks. After 4 weeks, serum triglyceride levels were significantly lower in rat fed with diet 2 compared with those fed with diet 3 and diet 4. Serum cholesterol levels were not significantly different among the rats fed with five diets except those rats fed with diet 2 showed significantly higher serum cholesterol than rats fed with diet 5. The data indicate that dietary fiber diet 2 containing 6% unpolished rice, 18% mung bean, 30% sweet corn and 40% nata de coco significantly reduced serum triglyceride in the experimental rats.